Customer Satisfaction with Digital Banking in India: Exploring the Mediating Role of Demographic Factors - Kamboj, Neha; Singh, Gurcharan (Indian Journal of Computer Science, 2018)
Consumers carry out financial transactions over the internet through a bankâ€™s website in digital banking. Thus, this form of banking has fascinated customers. The splendid innovation in technology and hard-hitting blend of banking with information technology created a paradigm shift in the banking industry. This study explored customer satisfaction with digital banking in India by evaluating the role of demographic factors. Various hypotheses were formulated. It assessed the demographical factors that are significant in finding the satisfaction of customers with digital banking. Banks in India do not employ their websites strategically to enhanceÂ customer relationship or add real value. Digital customers are anxious about the slow speed of the internet and the lack of security features. All these can be dealt by the management of banks and once started strategically, banks can further gear up the confidence of digital customers and more and more customers will turn to digital banking in India. Once customers are influenced about the diverse advantages of digital banking, they will start asking for other services from banks.